A Levinasian Reconstruction of the Political Significance of Vulnerability - Mao, Xin (2019)
The concept of vulnerability has been renewed in meaning and importance over recent decades. Scholars such as Judith Butler, Martha Fineman and Pamela Sue Anderson have endeavored to redeem vulnerability from its traditional signification as a negative individual condition, and to reveal the positive meaning of vulnerability as a transformative call for solidarity, equality and love. In this paper we examine the newly constructed positive understanding of vulnerability, and argue that the current way of pursuing this positive understanding affirms a merely functional positivity. In the recent accounts, vulnerability is still a status to avoid, yet functions positively as a corrective force to the environment that produces vulnerability. We will try to find an essential way of designating the positivity of vulnerability by revisiting the philosophical discussion on vulnerability in Emmanuel Levinas. We will argue that Levinas's notion of vulnerability is positive in a sense which goes beyond the purely functional; it is seen as essential for his definition of humanity. Yet compared to the contemporary discussion, Levinas's notion of vulnerability lacks a direct social political meaning. We will tentatively explore how the essential positivity drawn from Levinas can provide a new way to construct the political significance of vulnerability.
Keywords: Disruption; essential positivity; ethical subjectivity; functional positivity; Vulnerability